Making the most out of renewable energy opportunities: Lessons learned from a regional strategic mapping approach. Issue 1 (1st October 2018) - Leseure, Michel; Robins, Dawn; Wall, Graham; Jones, Dylan
Abstract : Purpose: Offshore renewable energy technologies provide many new opportunities for coastal regions around the world, and although the energy policy literature has documented the success stories of many "first mover" regions, there is little guidance for "second mover" or "follower" regions. This paper aims to investigate the strategic challenges faced by coastal regions in the Channel area that are not first movers. Design/methodology/approach: The authors use a multiple case study approach to analyse the behaviour of regional stakeholders when planning and assessing their participation in the renewable energy sector. Findings: The paper reveals the tendency of regional planners to idealise investments in renewable energy. The negative consequences of idealisation are inadequate strategic visions. Research limitations/implications: The findings are only relevant in the context of the regions that are part of the case study. Practical implications: The paper illustrates how idealisation of technology or strategy is created and how it impacts strategic decision-making. It also discusses how to address idealisation. Social implications: Although much of the energy policy literature discusses the challenge of social acceptance, this paper documents an opposite phenomenon, idealisation. There is a need in the energy sector to find a middle ground between these two extremes. Originality/value: The paper provides evidence and a theoretical analysis of a decision-making bias, idealisation, which is not discussed in the literature.